Friendship Networks and Delinquency: The Relative Nature of Peer Delinquency - Haynie, Dana L. (Journal of quantitative criminology, 2002)
Although acknowledging the importance of adolescent friendships in the etiology of delinquency, prior studies have yet to provide a detailed examination of the role of actual friendship networks in delinquency. Using data from the National Longitudinal Study of Adolescent Health (1995–1996), this study's incorporation of friendship networks allows for a more rigorous conceptualization and measurement of peer delinquency based on carefully defined networks of adolescent friendships. Findings illustrate that friendship networks are very heterogenous in terms of members' participation in delinquent behavior with the majority of adolescents belonging to networks containing both delinquent and non-delinquent friends. In support of differential association's premise that delinquent behavior is influenced by the ratio of definitions favorable to those unfavorable to law violation (Sutherland, 1947), the proportion of delinquent friends in a respondent's network is most strongly associated with respondents' subsequent delinquency. This relative measure of peer delinquency is preferable to a measure of the absolute level of delinquency occurring by friends, the average delinquency committed by friends, or the absolute number of delinquent friends. Enmeshment in a friendship network where consensus about the appropriateness of delinquency is maximized (i.e., all friends are delinquent or non-delinquent) most effectively constrains the behaviors of network members to resemble the groups' behavior.